2020
DOI: 10.1038/s41467-020-16561-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable tin perovskite solar cells enabled by amorphous-polycrystalline structure

Abstract: Tin perovskite solar cells (TPSCs) have triggered intensive research as a promising candidate for lead-free perovskite solar cells. However, it is still challenging to obtain efficient and stable TPSCs because of the low defects formation energy and the oxidation of bivalent tin; Here, we report a TPSC with a stable amorphous-polycrystalline structure, which is composed of a tin triple-halide amorphous layer and cesium-formamidinium tin iodide polycrystals. This structure effectively blocks the outside oxygen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
136
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 44 publications
3
136
0
Order By: Relevance
“…[ 14–16 ] However, compared with hybrid MASnI 3 and FASnI 3 PSCs of a significant leap in PCE over 10%, the potential application of all‐inorganic CsSnI 3 PSCs seriously suffered from the limitation of a low PCE of only around 5%. [ 17–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 14–16 ] However, compared with hybrid MASnI 3 and FASnI 3 PSCs of a significant leap in PCE over 10%, the potential application of all‐inorganic CsSnI 3 PSCs seriously suffered from the limitation of a low PCE of only around 5%. [ 17–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Note that the back-contact electrodes of these regular planar or mesoscopic devices were made by thermal evaporation of silver metal under high vacuum condition that is limited to their future industrial scalability. While the planar devices adopt ~200 nm thickness, closely associated with the effective charge diffusion length, for high-performance tin perovskites in solar cells, 14,15,27,28,[32][33][34]41 the 1 μm thick Al 2 O 3 insulating film in the mesoscopic devices is too harsh in terms of effective charge carrier diffusion for the tin perovskites. The further improvement in PCE is likely made by decreasing the Al 2 O 3 thickness.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…9 Such tin-based perovskites have been extended to other applications such as transistors, 10 photodetectors, 11 light-emitting diodes 12 and lasers. 13 For highperformance PSC, tin perovskites have evolved on suppressing oxidation of tin (from Sn 2+ to Sn 4+ ), pinholes and surface defects while improving crystallinity through an exploration of hybrid cations or anions, [14][15][16][17][18][19][20][21][22][23] additives [24][25][26][27][28][29][30][31][32][33] and interfacial engineering. [34][35][36][37] The additive approach is effective regardless of the type of tin perovskite and its interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] Herein it is shown that the addition of more MAAc during synthesis both inhibits the crystallization reaction, and increases the rate of desolvation, leading to formation of amorphous perovskite films and the incorporation of acetate in the films. The promising passivating properties of these films on crystalline perovskite, along with recent results using amorphous tin halide films to improve perovskite solar cells, [ 14 ] bring up the intriguing possibility of using amorphous passivating contacts for record solar cell performance, as has been demonstrated with crystalline silicon. [ 10,15 ]…”
Section: Introductionmentioning
confidence: 99%